Análisis de caudal y velocidad de sedimentación de las aguas residuales del campus CEASA como insumo fundamental para el funcionamiento de la planta de tratamiento de agua residuales - Flores Acosta, Ana Marife (2024)
The aim of this research project was to carry out a detailed analysis of the flow dynamics and sedimentation rate of wastewater at the CEASA Campus in order to propose an appropriate sedimentation process. For which, an average daily flow was determined to define adequate operating conditions of the treatment line; establishing the methodology for the determination of the flow, also a primary treatment line was implemented to establish operating parameters in the implementation of the different sanitation processes by means of physical-chemical parameters; where, the quality of the water resource was analysed and the sedimentation speed was determined. By means of a qualitative and quantitative approach, since the quantitative data helped to observe the overall picture, while the qualitative data provided detailed information. This was complemented by means of analytical and experimental research, in order to have a better approach to the research problem, which was done by carrying out gauging, taking and analysing samples; in addition, a vertical sedimentation column was implemented. The results of the analysis showed an average daily flow of 1.09 m3/h, as well as the identification of high levels of COD, total solids and turbidity, while the sedimentation efficiency showed variability, highlighting the influence of the initial height in relation to time. In conclusion, these findings highlight the urgency of addressing the identified pollution levels and implementing measures to improve the efficiency of wastewater treatment at the CEASA Campus. This study provides a solid basis for future research and actions to mitigate negative environmental impacts and ensure water quality in the area.